Hungarian Monitoring, 21 October 1989 . [Magyar rádiófigyelő], 1989. október 21 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Premier Ryzhkov: economic situation in the USSR is exceptionally tense - Bulgarian CP's stance on reforms Domestic Affairs: - Hungarian Democratic Forum (MDF) national conference - Arrow Cross leaflets scandal - Ferenc Somogyi's speech at UN General Assembly - Hungarian Socialist Party (MSZP) recruitment festival - Timisoara minister László Tőkés writes letter to Ceauşescu - Petőfi research - Workers' Militia abolished without legal successor - Preparations for October 23 celebrations Economy: - Tamás Beck gives lecture to Austrian politicians on economic reforms - Management and property relations - Hungarocoop Külpolitika: - Rizskov miniszterelnök szerint rendkívül feszült a gazdasági helyzet a Szovjetunióban - A bolgár KP viszonya a reformokhoz Belpolitika: - MDF országos konferencia - Nyilaskeresztes röplap botrány - Somogyi Ferenc felszólalása az ENSZ közgyűlésen - MSZP tagtoborzó fesztivál - Tőkés László temesvári lelkész tiltakozó levelet írt Ceauşescunak - Petőfi-kutatás - Jogutód nélkül megszűnt a Munkásőrség - Készülődés az okt.23-i ünnepségekre Gazdaság: - Beck Tamás osztrák politikusoknak tartott előadást a gazdasági reformokról - Gazdálkodás és tulajdonviszonyok - Hungarocoop